Nonvolatile and ultra-low-loss reconfigurable mode (De)multiplexer/switch using triple-waveguide coupler with Ge2Sb2Se4Te1 phase change material - Weifeng Jiang (Nature Portfolio, 2018)
Abstract Mode-division multiplexing (MDM) is a promising approach to dramatically enhance the transmission capacity. A reconfigurable mode (De)multiplexer/switch (RMDS) is a key component for the flexible mode routing in the MDM network. A nonvolatile and ultra-low-loss RMDS is proposed via a triple-silicon-waveguide directional coupler with the Ge2Sb2Se4Te1 (GSST) phase change material (PCM). The nonvolatile property of GSST makes it attractive to reduce the switching power-consumption. Benefiting from the low loss of the GSST-PCM at both amorphous and crystalline states, an RMDS with an ultra-low loss and a high extinction-ratio can be realized. The proposed RMDS is optimally designed by using the full-vectorial finite element method and 3D full-vectorial finite difference time domain method. The numerically simulated results show that a compact RMDS is with the extinction ratios of 18.98 dB and 22.18 dB, ultra-low insertion losses of 0.10 dB and 0.68 dB for the “OFF” and “ON” states, respectively at the operating wavelength of 1550 nm. An ultra-wide bandwidth of 100 nm is achieved for both the “OFF” and “ON” states.